Changes in Pain Score Associated With Clinically Meaningful Outcomes in Children With Acute Pain. (19th February 2019) - Tsze, Daniel S.; Hirschfeld, Gerrit; von Baeyer, Carl L.; Suarez, Leonor E.; Dayan, Peter S.
Abstract: Background: Identifying changes in pain score associated with clinically meaningful outcomes is necessary when using self‐report measures to assess pain in children. We aimed to determine the changes in pain score associated with a minimum clinically significant difference (MCSD), ideal clinically significant difference (ICSD), and patient‐perceived adequate analgesia (PPAA) and to evaluate for differences based on initial pain intensity and patient characteristics. Methods: This was a cross‐sectional study of children 6 to 17 and 4 to 17 years old who were assessed using the Verbal Numerical Rating Scale (VNRS) and Faces Pain Scale–Revised (FPS‐R), respectively. Children qualitatively described any endorsed change in pain score; those who received an analgesic were asked if they wanted additional analgesics to decrease their pain intensity. We used a receiver operating characteristic curve–based methodology to identify changes in pain score associated with "a little less" and "much less" pain (MCSD and ICSD, respectively) and patients declining additional analgesics because of adequate analgesia (PPAA). Results: We enrolled 431 children with painful conditions. For the VNRS, raw change and percent reductions in pain scores associated with MCSD, ICSD, and PPAA were 2/10 and 20%, 3/10 and 44%, and 2/10 and 29%, respectively, and for the FPS‐R, 2/10 and 33%, 4/10 and 60%, and 4/10 and 40%, respectively. Raw change in pain scores increased with increasing initial pain intensity, but percent reductions remained stable. There were no significant differences based on patient characteristics such as age, sex, and race/ethnicity. Conclusion: Our findings provide patient‐centered outcomes in children that are suitable for designing trials and are generalizable across patient characteristics.